Dupilumab‐associated head and neck dermatitis is associated with elevated pretreatment serum Malassezia‐specific IgE: a multicentre, prospective cohort study. (19th April 2022) - Kozera, Emily; Stewart, Thomas; Gill, Kyra; De La Vega, Mae Anne; Frew, John W.
Abstract : Dupilumab associated head and neck dermatitis is incompletely understood. This prospective multicentre prospective study identified baseline Malassezia ‐specific IgE as associated with the development of Dupilumab associated head and neck dermatitis.